High‐density mapping of de novo focal atrial tachycardias using a new software: Protected low‐voltage areas by zones of conduction delay. Issue 4 (14th June 2020) - Letsas, Konstantinos P.; Efremidis, Michael; Bazoukis, George; Dragasis, Stylianos; Megarisiotou, Athanasia; Mililis, Panagiotis; Saplaouras, Athanasios; Vlachos, Konstantinos; Asvestas, Dimitrios; Valkanas, Kosmas; Tse, Gary; Sideris, Antonios
Abstract: Background: The pathophysiological mechanism of focal atrial tachycardias (AT) remains obscure. Methods: Fifteen patients (6 males, age 45 ± 18) with focal AT underwent high‐density activation mapping using a new software called extended early‐meets‐late (EEML). Results: Irrespective of the arrhythmia mechanism, low bipolar voltage fractionated signals (0.14 ± 0.10 mV) were seen at the earliest activation site. The mean low‐voltage area (LVA) at the earliest activation site was 3.2 ± 1.0 cm 2 . EEML mapping revealed zones of conduction delay at the borders of LVAs. Conclusions: LVAs protected by zones of slow conduction appears to play an important role in the initiation and maintenance of focal ATs. Abstract : Low‐voltage areas protected by zones of slow conduction appear to play an important role in the pathophysiology of focal ATs.